Tinjauan Hukum Terhadap Perjanjian Kredit Jual Beli Sepada Motor Di PT. Asli Motor Klaten - Setiawan, Ari; , Darsono, S.H., M.H (2016)
This study aims to investigate the implementation of a credit agreement of sale and purchase of motorcycles in PT. Genuine Motor Klaten and obstacles that arise and solutions in the credit agreement of sale and purchase of motorcycles in PT. Genuine Motor Klaten. The research method using normative juridical approach to the specification of research in concreto. The data source consists of primary legal materials, secondary and tertiary. Data were collected through interviews, literature and the literature, then the data were analyzed by descriptive qualitative. The results showed that the implementation of the pact vehicle loans between companies selling to the consumer / buyer is credit relationships vehicle mutually beneficial and mutually agreed, but legally the two sides have a position that is not balanced because the consumer / buyer is in a weak position that can only receive motorcycle loan agreement from the company seller, then both sides should have a good faith and a strong commitment to implement the agreement on vehicle loans with the principle of mutual benefit. Obstacles encountered in the implementation of the agreement is frequent misinterpretation of the contents of the agreement made by the consumer / buyer resulting knowledge is not good, and did not carefully read the contents of the agreement signed today.